The Genome Landscape of the African Green Monkey Kidney-Derived Vero Cell Line - Osada, Naoki; Kohara, Arihiro; Yamaji, Toshiyuki; Hirayama, Noriko; Kasai, Fumio; Sekizuka, Tsuyoshi; Kuroda, Makoto; Hanada, Kentaro (DNA research, 2014)
Continuous cell lines that originate from mammalian tissues serve as not only invaluable tools for life sciences, but also important animal cell substrates for the production of various types of biological pharmaceuticals. Vero cells are susceptible to various types of microbes and toxins and have widely contributed to not only microbiology, but also the production of vaccines for human use. We here showed the genome landscape of a Vero cell line, in which 25,877 putative protein-coding genes were identified in the 2.97-Gb genome sequence. A homozygous ∼9-Mb deletion on chromosome 12 caused the loss of the type I interferon gene cluster and cyclin-dependent kinase inhibitor genes in Vero cells. In addition, an ∼59-Mb loss of heterozygosity around this deleted region suggested that the homozygosity of the deletion was established by a large-scale conversion. Moreover, a genomic analysis of Vero cells revealed a female Chlorocebus sabaeus origin and proviral variations of the endogenous simian type D retrovirus. These results revealed the genomic basis for the non-tumourigenic permanent Vero cell lineage susceptible to various pathogens and will be useful for generating new sub-lines and developing new tools in the quality control of Vero cells.